Crystal field aspects of vibrational spectra - Hancock, Robert Douglas (Department of Chemistry, 2016)
Crystal Field Theory (C.F.T.), and its congeners, Ligand Field Theory (L.F.T.) and Molecular Orbital Theory (M.O.T.), have been most successful in explaining many of the properties of transition metal complexes. This is particularly true of their electronic spectra, magnetochemistry and chemical thermodynamic properties. However, these theories have been ignored in relation to the explanation of changes observed in the infrared spectra of series of transition metal complexes on change of central cation. The purpose of this work is to examine such changes in the light of these theories. The basis of the above theories is the splitting of the inner orbitals of the metal ions, due to the field of the ligands surrounding them. The field may be considered to arise from electrostatic repulsion by the ligand electrons (C.F.T.), or as a result of the chemical bonding between the central cation and the ligands (L.F.T. and M.O.T.). The result of this inner orbital splitting is stabilisation of the electrons of the orbital, as comparred with their energy in the absence of the field.